‘I was having an anxiety attack and they pepper sprayed me': police apprehension in mental health contexts in Australia - Randall, Rory (Policing and society, 2025)
Police attendance in mental health contexts is often traumatic for the person in crisis, their family and first responders. Existing literature on police involvement in mental health responses tends to focus on police perspectives. Scholarship exploring lived experience perspectives is limited, yet is crucial for informing programmes, policies and reforms. We present findings from one of the first projects co-produced with people with lived experiences of being apprehended by police under mental health legislation. Interviews were conducted with twenty participants who had experience(s) of police apprehension across Australia. Findings highlight the social disadvantage experienced by participants prior to being apprehended and that use of force (such as tasering, pepper spraying and restraining in locked police vans) was common and over-used. Our study identified that police apprehension has lasting and wide-ranging impacts, leading to loss of employment, trauma, property damage, negative self-perceptions, discrimination, and fear of future police responses. Some participants were also apprehended by police while experiencing family violence and were misidentified as perpetrators. We argue police use of force mirrors the use of force within mental health services, with participants not experiencing a clear separation between police and mental health responses. The article shares participants’ ideas for change, including response models based on human rights, police non-attendance and peer-led initiatives. Our findings suggest the need for investment in alternatives to police responses and further research involving lived experience perspectives to inform out understanding of mental health crisis responses.